2020
DOI: 10.1021/acs.est.0c00044
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Abandoned Well Sites Using Database Records and Aeromagnetic Surveys

Abstract: Oil and natural gas are primary sources of energy in the United States. Improved drilling and extracting techniques have led to a renewed interest in historic oil and gas fields, but limited records of legacy wells make new drilling efforts more difficult, as abandoned wells may provide conduits for liquids and gases to migrate into groundwater reservoirs or the atmosphere. Well finding using aeromagnetic surveys pinpoints the location of steel-cased wells, detecting both active and abandoned wells, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…Across the United States, there are many states with oil production dating back to the 19th century, including California (Brandt, 2011) and Texas. A recent study scaling up results from database records and aeromagnetic surveys estimates that the average number of drilled wells in the United States is 6,037,587, with 1,159,689 being abandoned (Saint-Vincent et al, 2020b).…”
Section: Number Of Active and Inactive Oil And Gas Wellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Across the United States, there are many states with oil production dating back to the 19th century, including California (Brandt, 2011) and Texas. A recent study scaling up results from database records and aeromagnetic surveys estimates that the average number of drilled wells in the United States is 6,037,587, with 1,159,689 being abandoned (Saint-Vincent et al, 2020b).…”
Section: Number Of Active and Inactive Oil And Gas Wellsmentioning
confidence: 99%
“…In addition, government databases do not provide sufficient information to assess whether a well is plugged properly. Overall, aside from vented plugged wells, measurements show lower average rates of methane emissions from plugged wells than unplugged wells Townsend-Small et al, 2016;Saint-Vincent et al, 2020a;Williams et al, 2020); nonetheless, leakage to groundwater and/or to the atmosphere can occur at unplugged and deteriorating or poorly plugged wells (Kell, 2011;McMahon et al, 2018).…”
Section: Barriers and Limitations Of Well Pluggingmentioning
confidence: 99%
“…The average distance between a well identified in the field and an OCC orphan well site was 1.0 ± 0.9 km. Well locations from public databases are not often reliable sources for accurate well locations or counts (Saint‐Vincent, Sams, et al, 2020). Differences in well locations are likely the result of different spatial localization technologies (GPS coordinates are not required for well permits in Oklahoma; Oil & Gas Conservation Division, 2018), or the result of improper conversion between coordinate systems.…”
Section: Data and Resultsmentioning
confidence: 99%
“…In contrast, there are 88,849 unplugged abandoned wells and 125,200 plugged abandoned wells reported for the Appalachian Basin (DrillingInfo. Wells Data, 2019) (although reports suggest public databases are inaccurate and incomplete (Saint‐Vincent, Sams, et al, 2020), and there could be 305,000–390,000 abandoned wells in Pennsylvania alone (Dilmore et al, 2015). Using the Appalachian Basin EF of 670 g/day for unplugged wells from the GHGI (U.S. Environmental Protection Agency, 2020), we calculated the emissions of unplugged wells as 540,000 mt CO 2 e/year; yet based on well predictions the emissions could be as high as 1.8–2.4 million mt CO 2 e/year in Pennsylvania alone (plugged wells in the Appalachian Basin have an EF of 0 g/day in the GHGI although this likely underrepresents emissions) (Dilmore et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…11 Although data remain quite limited, emissions rates appear to vary across well types (i.e., oil or gas wells), geology, and-most importantly-plugging status, with unplugged wells typically emitting more methane than plugged wells. e.g., 2,20,21,19,[22][23][24] Although there are considerable uncertainties surrounding the magnitude of environmental risks, some recent evidence has suggested that proximity to unplugged oil and gas wells reduces property values considerably. In a working paper, Shappo 25 estimates that property values are roughly $15,000 (11%) lower for Pennsylvania homes within two kilometers of unplugged wells compared with similar homes that are not close to unplugged wells.…”
Section: Risks Of Unplugged Abandoned Wellsmentioning
confidence: 99%